2015
DOI: 10.1080/17455030.2015.1042092
|View full text |Cite
|
Sign up to set email alerts
|

Study on the polarization properties of electromagnetic waves with arbitrary magnetic declination in magnetized plasma

Abstract: The polarization characteristics of oblique incidence electromagnetic waves in magnetized cold plasma layer are studied using the finite-difference timedomain (FDTD) method based on the trapezoidal recursive convolution (TRC) technology. The TRC-FDTD formulations are derived in detail and are confirmed by computing the reflection and transmission coefficients for the elliptically polarized wave through a magnetized cold plasma slab with arbitrary magnetic direction. Particularly, when the propagation direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It is widely used to analyze electromagnetic wave transmission characteristics in plasma, such as through using the Wentzel-Kramer-Brillouin (WKB) method, scattering matrix method (SMM), finite-difference time-domain (FDTD) method. [14][15][16][17][18][19][20][21][22][23][24][25] Yu et al used the WKB method to study the transmission characteristics of terahertz waves in magnetized plasmas with different electron density distributions. [26] Numerical simulation results demonstrated that the plasma density, plasma slab thickness, plasma density models, and collision frequency significantly influence the attenuation and transmittance of terahertz waves.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used to analyze electromagnetic wave transmission characteristics in plasma, such as through using the Wentzel-Kramer-Brillouin (WKB) method, scattering matrix method (SMM), finite-difference time-domain (FDTD) method. [14][15][16][17][18][19][20][21][22][23][24][25] Yu et al used the WKB method to study the transmission characteristics of terahertz waves in magnetized plasmas with different electron density distributions. [26] Numerical simulation results demonstrated that the plasma density, plasma slab thickness, plasma density models, and collision frequency significantly influence the attenuation and transmittance of terahertz waves.…”
Section: Introductionmentioning
confidence: 99%